2011
DOI: 10.2298/vsp1107567d
|View full text |Cite
|
Sign up to set email alerts
|

Expression of regulatory proteins and proliferative activity in relation to phenotypic characteristics of upper urothelial carcinoma

Abstract: This investigation showed that only negative regulatory proteins of the cell cycle, p53 and p16, were significantly associated in UUC, while proliferative marker Ki-67 was in relation to the key phenotypic characteristics of UUC in the best way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Molecular tumor markers hold considerable promise for accurately predicting the recurrence and progression of NMIBC patients treated with BCG intravesical therapy. Deregulation of the cell-cycle machinery is common in bladder cancer, involving alterations in various proteins such as cyclin D1, Rb, p16, p21, p27, and p53 [ 5 , 6 ]. The value of pretreatment p53 overexpression on the prognosis of NMIBC patients treated with BCG has been widely studied and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular tumor markers hold considerable promise for accurately predicting the recurrence and progression of NMIBC patients treated with BCG intravesical therapy. Deregulation of the cell-cycle machinery is common in bladder cancer, involving alterations in various proteins such as cyclin D1, Rb, p16, p21, p27, and p53 [ 5 , 6 ]. The value of pretreatment p53 overexpression on the prognosis of NMIBC patients treated with BCG has been widely studied and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In normal cells, p53 can induce cell cycle arrest at the G0/G1 phase and cell apoptosis; and when it is mutated, as in the case of several types of tumor, p53 loses its regulatory role and promotes tumor progression (32). Deregulation of cell-cycle machinery involving alterations in p53 is common in bladder cancer (33), breast cancer (34), lung cancer (35) and CRC (36). Significant differences in p53 staining between CRC tissues and normal control tissues have been reported in previous studies (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 16 eligible studies were identified (Figure 1). [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The main characteristics of the included studies, which were all retrospective, are summarized in Table 1 and Table 2. Among 16 studies, a total of 2030 UTUC patients ranging from 20 to 732 patients per study were reported.…”
Section: Study Selection and Characteristicmentioning
confidence: 99%